2012
DOI: 10.1097/igc.0b013e3182370f2e
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Clinical Significance of Sperm-Associated Antigen 9 in Patients With Endometrial Carcinoma

Abstract: SPAG9 is positively expressed in endometrial cancer, and with a high humoral immune response in patients. It may serve as a new type of endometrial cancer markers for early detection, diagnosis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 15 publications
2
26
0
Order By: Relevance
“…They also found that SPAG9 was expressed in metastatic lymph nodes. Cases with grade 3 tumors had significantly higher SPAG9 levels in their serums, when compared to cases with grade 1-2 tumors (Yu et al, 2012). They stated that SPAG9 levels were similar between cases of endometrial hyperplasia and completely normal endometrium.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…They also found that SPAG9 was expressed in metastatic lymph nodes. Cases with grade 3 tumors had significantly higher SPAG9 levels in their serums, when compared to cases with grade 1-2 tumors (Yu et al, 2012). They stated that SPAG9 levels were similar between cases of endometrial hyperplasia and completely normal endometrium.…”
Section: Discussionmentioning
confidence: 94%
“…SPAG9 gene is located at the chromosome 17q21, which is a region involved in amplification and expression of cancer-related genes (Jagadish et al, 2005b). Although it was originally thought to be expressed exclusively in testis, ongoing research revealed SPAG9 expression in numerous tumors originating from various sites and organs such as brain, thyroid, breast, lung, kidney, colon, ovary, cervix, and endometrium (Garg et al, 2008, Garg et al, 2009a, Garg et al, 2009b, Kanojia et al, 2009, Kanojia et al, 2011, Yu et al, 2012, Wang et al, 2013, Yi et al, 2013. In a study by Garg et al (2007), SPAG9 expression and host immune responses were investigated in epithelial ovarian cancer (EOC) specimens and human ovarian cancer cell lines (Garg et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations